Compartmental Modeling Approach: Application on Transdermal Delivery for In Vitro Drug Permeation Mechanism Analysis - Pawestri, Sekar Ayu; Nugroho, Akhmad Kharis; Lukitaningsih, Endang; Purwantiningsih (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2021)
Compartmental modeling analysis was used to understand the transport mechanism of drugs in biological systems by computation presented as intercompartmental flows or material. This study was aimed to implement compartmental modeling analysis for in vitro permeation studies in transdermal delivery. The cumulative drug transported versus time were obtained based on the previous report and implemented the two structural different proposed models. WinSAAM software (Windows-based Simulation Analysis and Modeling-WinSAAM Project Group, University of Pennsylvania) was used to analyze data with compartmental analysis. The chosen models were selected through visual and numeric evaluation. The best model had been chosen and could figure out the drug transport kinetics in the biological system. The compartmental modeling approach was helpful used in understanding drug transport mechanisms in transdermal delivery and effectively estimate the drug transport parameter.